The use of educational technology in the light of international standards as a reference to measure the effectiveness of using the educational process - استخدام تكنولوجيا التعليم في ضوء المعايير الدولية بوصفها مرجعية لقياس فاعلية الاستخدام في العملية التعليمية - Nasser Albusaidi, Faisal Ali; Sahrir, Muhammad Sabri (OCERINT International Organization Center of Academic Research, 2020)
This descriptive, analytical study reviews the most important aspects related to measuring the effectiveness of the educational technology used based on international standards for using educational technology, as one of the important benchmarks for building on its educational dimensions and measuring the effectiveness of the use of educational technology. The problem lies in the lack of national standards that can be relied upon in many educational systems in educational institutions to measure the effectiveness of the use of educational technology, as well as the lack of adoption of building national standards on which to base the empowerment of education personnel in the use of educational technology. The study aims to introduce the dimensions of educational technology, its role in the teaching and learning process, and to define international standards for the use of educational technology related to teachers, students or educational leaders. Through the descriptive analytical approach, the study reached several results, the most important of which are: the components of educational technology greatly influence the improvement of the educational process and raise the level of quality in achieving educational goals. Information and communication in education.